HEALTH EDUCATION AND THE CONTROL OF UROGENITAL SCHISTOSOMIASIS: ASSESSING THE IMPACT OF THE JUMA NA KICHOCHO COMIC-STRIP MEDICAL BOOKLET IN ZANZIBAR. (18th July 2016) - Stothard, J. R.; Khamis, A. N.; Khamis, I. S.; Neo, C. H. E.; Wei, I.; Rollinson, D.
Summary: Endeavours to control urogenital schistosomiasis on Unguja Island (Zanzibar) have focused on school-aged children. To assess the impact of an associated health education campaign, the supervised use of the comic-strip medical booklet Juma na Kichocho by Class V pupils attending eighteen primary schools was investigated. A validated knowledge and attitudes questionnaire was completed at baseline and repeated one year later following the regular use of the booklet during the calendar year. A scoring system (ranging from 0.0 to 5.0) measured children's understandings of schistosomiasis and malaria, with the latter being a neutral comparator against specific changes for schistosomiasis. In 2006, the average score from 751 children (328 boys and 423 girls) was 2.39 for schistosomiasis and 3.03 for malaria. One year later, the score was 2.43 for schistosomiasis and 2.70 for malaria from 779 children (351 boys and 428 girls). As might be expected, knowledge and attitudes scores for schistosomiasis increased (+0.05), but not as much as originally hoped, while the score for malaria decreased (−0.33). According to a Kolmogorov–Smirnov test, neither change was statistically significant. Analysis also revealed that 75% of school children misunderstood the importance of reinfection after treatment with praziquantel. These results are disappointing. They demonstrate that it is mistaken to assume that knowledge conveyed in child-friendly booklets will necessarily be interpreted, and acted upon, in the way intended. If long-term sustained behavioural change is to be achieved, health education materials need to engage more closely with local understandings and responses to urogenital schistosomiasis. This, in turn, needs to be part of the development of a more holistic, biosocial approach to the control of schistosomiasis.